SPAREPARTS SALES INFORMATION SYSTEM ON JAYA MAKMUR MOTOR REPAIR USING MICROSOFT VISUAL BASIC 6.0 AND MICROSOFT ACCESS 2003 - Agustinus Edi Priyanto; Eriek Orlando (Jurnal Sistem Informasi, 2009)
The need of information is very important and its no exception in theautomotive sector. Good activity at a company or organization is determined bythe available information. This is due to make the right decisions requireaccurate data to be quickly and easily understood. This is where the programdatabase system as a computerized data provider must be able to provideinformation in a short time and easy to read. In the automotive workshops, suchas motor workshops that still use manual system to process data of sales, data ofprice and stocks of spare parts has not been able to represent the need of thatinformation, so the result of information obtained is less accurate and takesmuch longer. Therefore, existing data must be managed effectively. MicrosoftVisual Basic 6.0 and Microsoft Access 2003 are some examples of the manysoftware tools that can solve the problem.